Effects of carbon dioxide therapy on the healing of acute skin wounds induced on the back of rats - Penhavel,Maria Vitória Carmo (2013)
PURPOSE: To evaluate the healing effect of carbon dioxide therapy on skin wounds induced on the back of rats. METHODS: Sixteen rats underwent excision of a round dermal-epidermal dorsal skin flap of 2.5 cm in diameter. The animals were divided into two groups, as follows: carbon dioxide group - subcutaneous injections of carbon dioxide on the day of operation and at three, six and nine days postoperatively; control group - no postoperative wound treatment. Wounds were photographed on the day of operation and at six and 14 days postoperatively for analysis of wound area and major diameter. All animals were euthanized on day 14 after surgery. The dorsal skin and the underlying muscle layer containing the wound were resected for histopathological analysis. RESULTS: There was no statistically significant difference between groups in the percentage of wound closure, in histopathological findings, or in the reduction of wound area and major diameter at 14 days postoperatively. CONCLUSION: Under the experimental conditions in which this study was conducted, carbon dioxide therapy had no effects on the healing of acute skin wounds in rats.